TOXIC IMPACTS OF TWO ORGANOPHOSPHORUS PESTICIDES ON THE ACETYLCHOLINESTERASE ACTIVITY AND BIOCHEMICAL COMPOSITION OF FRESHWATER FAIRY SHRIMP STREPTOCEPHALUS DICHOTOMUS - ARUN KUMAR M.S; A. JAWAHAR ALI; A. JAWAHAR ALI (International Journal of Pharma and Bio Sciences, 2013)
The 96 hrs LC50 values for malathion and glyphosate was determined to be 9.1 ppm and 5.5 ppb, respectively on the fairy shrimp, Streptocephalus dichotomus preadults. The 1/5th of 96 hrs LC50 of malathion (2.0 ppm) and glyphosate (1.1 ppb) respectively was chosen. The sub lethal toxic effect of each of these pesticides on the acetylcholinesterase activity (AchE) of S. dichotomus was assayed on days 0 and 15th of exposure, and found to be significantly decreased (0.13±0.006 nmol/mg/min) in malathion than in glyphosate when compared with control. Furthermore, the contents of selected biochemical constituents (total protein, carbohydrate and lipid) of S. dichotomus were estimated on ‘0’, 15th and 30th days of exposures, and found to be decreased significantly on 30th day in both the pesticides when compared to control. The results indicated the fact that these pesticides are toxic to S. dichotomus at the tested concentrations.